PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA PEGAWAI DINAS PERUMAHAN KAWASAN PERMUKIMAN DAN PERTANAHAN KABUPATEN BOGOR - Yasnimar Ilyas; Adi Haniefa; Mochammad Adam Husein; Muchammad Hamdani; Syaiful Anwar (Economicus, 2024)
This research aims to assess the influence of leadership style and organizational culture on employee effectiveness in the Office of Housing, Settlement, and Land Affairs in Bogor Regency. A quantitative research with an explanatory survey approach was conducted, utilizing both primary and secondary data sources from 77 respondents. The results of multiple linear regression analysis indicate a significant impact of leadership style (X1) and organizational culture (X2) on work effectiveness. Partially, leadership style has a significant influence, while organizational culture has a positive effect albeit with a lower level of significance. The leadership style variable plays a dominant role in influencing work effectiveness with a contribution of 37.1%. Overall, leadership style and organizational culture collectively have a positive impact on work effectiveness by 27.4%, while the remaining 72.6% is influenced by other factors not addressed in this study.